Food Policy and the Choice of Trade Regime - Oyejide, Ademola T. (International Food Policy Research Institute, 1987)
A consensus is emerging, especially among academics, policy analysts, and the more enlightened politicians on the need for urgent and sustained action to provide both short-term and long-term solutions to Africa's food producers. However, it is still debatable whether we fully understand the scope of the food problem and the factors responsible for it. It is important to make a clear distinction between long-term and shortterm aspects of food policy and food security relationships. It is obvious that the long term is not necessarily a series of short terms and that long-term considerations are influenced by short-term responses to food policy problems. Thus, the long-term orientation of the following discussion is not to be taken as implying that the short-term elements of food policy issues (for example, food supply instability and insecurity) are not closely related to the choice of trade regime (that is, to tariff, quota, and exchange rate policies). Rather, it is an attempt to obtain the sharpest possible focus by concentrating on a limited set of issues.